(untitled) (Journal of the College of Languages (JCL), 2021)
The United States government allowed Native Americans to abandon their reservations in the 1950s and 1960s. The historical, social, and cultural backgrounds shaped the forms and themes of works by American Indian writers who urged people to refuse their culture’s sense of shame. Moreover, their behavior corresponded with the restoration of individuals to their rituals after disappointment, loss of sense of life, and mental illness performed from the influence of mainstream American society. Among these writers, N. Scott Momaday and Leslie Marmon Silko participate in similar interest in portraying characters caught between indigenous beliefs and white mainstream standards. The construction of national identity in the first modernist Native American Novel, House Made of Dawn (1968) by N. Scott Momaday is tackled in this research. This novel illustrates the healing tale of a young Native American man who, after his return from military service in World War II, suffers from spiritual and psychological illness. The protagonist is isolated from his parents due to his traumatic experience of a foreign war and his problematic genealogy that stems from the orphanage. He is isolated from the land that offers his identity and his culture. In order to gain a consistent sense of identity with the aid of oral traditions and ancient ceremonials of Navajo and pueblo cultures, he begins a ritualistic journey that ultimately leads him to reintegrate with his people and culture. This research illustrates how the construction of national identity is a critical theme for American Indians and contemporary Native American authors.